Marching forward to the past? : Challenges and prospects for the new theology of land in Zimbabwe - Maposa, Richard S.; Hlongwana, James; Muguti, Tasara (European Journal of Sustainable Development, 2013)
The article seeks to delineate and evaluate some constraints that the new black farmers inthe former white commercial farms face in the backdrop of the contested land reformprogramme in Zimbabwe. Whereas there was euphoria in the manner the peasants‘occupied’ the commercial farms, but the current reality on the ground is pessimistic. Thestudy claims that instead of improving the quality of lives, the new black farmers appear tobe literally ‘marching forward tothe past’ in light of the continued challenges. This is how atheology of liberation comes to the fore. Methodologically, the descriptive method used apopulation sampling of fifty resettled farmers who occupiedCongela farm in Kwekwedistrict. This method was corroborated by the participant observations, questionnaires andinterviews as techniques to gather data fromthe field. This triangulation was necessary tofacilitate a holistic picture ofresource constraints faced by the resettled black farmers. Thestudy concludes by suggesting some recommendations which might help to promotesustainable development, justice and equality in Zimbabwe.